2023
DOI: 10.1186/s10194-023-01555-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional, hospital-based analysis of headache types using ICHD-3 criteria in the Middle East, Asia, and Africa: the Head-MENAA study

Abstract: Background Headaches are frequent neurological disorders that are yet to be unveiled and treated comprehensively worldwide. Bearing in mind that the distribution of headache subtypes in neurology clinics (NC) is essential for planning appropriate diagnostic and therapeutic approaches, the primary goals of this multi-centric study are to carry out inter-regional comparisons by using current diagnostic criteria with evaluations of neurologists to delineate headache burden. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Pain severity, as measured using an NRS, was different between the regions (p ¼ 0.002). In pairwise comparisons, it was observed that the patients in Africa (6.37 AE 2.14 [range, [3][4][5][6][7][8][9][10]) presented to the hospital with milder pain than those in Turkey (6.96 AE 0.09 [range, 1-10]), the Middle East (6.87 AE 0.30 [range, 2-10]), and Asia (6.86 AE 0.27 [range, 5-9]) (p ¼ 0.047). The density of headaches (the number of days with headache per month) was different between the regions (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain severity, as measured using an NRS, was different between the regions (p ¼ 0.002). In pairwise comparisons, it was observed that the patients in Africa (6.37 AE 2.14 [range, [3][4][5][6][7][8][9][10]) presented to the hospital with milder pain than those in Turkey (6.96 AE 0.09 [range, 1-10]), the Middle East (6.87 AE 0.30 [range, 2-10]), and Asia (6.86 AE 0.27 [range, 5-9]) (p ¼ 0.047). The density of headaches (the number of days with headache per month) was different between the regions (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The density of headaches (the number of days with headache per month) was different between the regions (p < 0.001). In pairwise comparisons, it was detected that the patients in Africa (5.93 ± 1.06 [0–30]) referred to the hospital with a lower density of headaches than those in Turkey (11.68 ± 0.53 [0–30]), the Middle East (15.97 ± 1.73 [230]), and Asia (11.19 ± 2.15 [0–30]) (p < 0.001) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This interaction between the hypersensitivities of patients with migraine is thought to result from the activation of cortical areas involved in modality upon visual stimuli in the fourth, seventh, and tenth rounds (median [IQR] 78. 1…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports in the Middle East, Asia, and Africa have shown that the prevalence of headache among adolescents is almost similar to that among adults; however, the epidemiology of headache is less investigated among adolescents than adults ( 2 ). Primary headache disorders among children and adolescents are a worldwide health problem ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%